Desenvolvimento Software Têxtil - Lusitano, Vasco Jorge Fortuna (2022)
The Fourth Industrial Revolution is a new phase of the textile industry. This uprising focuses on the connectivity and automation of manual processes, forcing textile companies to look for goods that make them go beyond the archaic level of outdated methods. After contacting an engineer in the textile area, with several years of experience, the need for companies in the sector to use a technology capable of handling and storing the data inherent to their methodologies was evident. Thus, the objective of idealizing and developing a solution oriented to the needs of the company in which the textile professional worked was aligned, namely Empresa Têxtil da Maganha. This document is divided into 7 chapters, each of which has its responsibilities, in more detail, the introduction, the state of the art, the value analysis, the requirements and design analysis, the implementation, the experimentation and evaluation and the conclusion. The initial part presents the context, approach, problems and objectives, in a perspective that invites the reader to understand the theme and seek a solution. Next, the planning and technical specification are presented, showing the state of the art decisions made. The technical description in the report highlights the requirements analysis and architectural design, followed by the details of the system implementation. With the development of the textile software disappearing, a quality solution was achieved, following the standards and models described.